The Knowns and Unknowns of Policy Instrument Analysis: Policy Tools and the Current Research Agenda on Policy Mixes - Capano, Giliberto; Howlett, Michael (SAGE open, 2020)
Policies are made and pursue their goals through policy instruments. Furthermore, policy instruments have become a relevant topic in many policy fields due to their theoretical and empirical relevance. The study of this field dates back to Lowi and others who developed many typologies and theories in classic works by authors such as Hood, Salamon, Linder and Peters, Peters and van Nispen, Schneider and Ingram, Lascomes and Le Galès, among others. This is important work that is linked closely to current research on policy design but, despite much effort, many fundamental issues remain unknown or understudied with respect to the topic. It is time to take inventory of the knowns and unknowns about policy tools. The current article examines four clusters of basic issues in the field which require further research.